Experiential teaching and learning in schools applying robots - Pántya, Róbert; Mucsics, F. László (Acta Carolus Robertus, 2024)
In the schooling system of the 21st century, there is a great need for new methods and tools that are capable of attracting and retaining the attention of students as digital natives, so experiential, experience-based teaching methods are particularly important. The recent large-scale development of tools in many schools (mostly with the help of EU funding) has made available the educational robot kits that are essential for their everyday pedagogical use. Furthermore, besides the purchase and applications of robots, teacher training courses have helped to familiarise many teachers with these new tools and methods. The most important question for the successful implementation of new robot-supported methods is the extent to which the use of these modern pedagogical tools is embedded in the everyday practice of individual schools, and the extent to which teachers have the courage to actively involve these robots and, of course, the pupils in the educational process. A good indicator of the successful use of robots in a school is the existence of a functioning robotics department and, unfortunately, inadequate practice can be indicated by the fact that these tools are kept in a locked, inaccessible cupboard, in such a way that pupils are often unaware of their existence. Robot kits are an incredible motivator for learners, so our work is looking at how these tools can be used to make learning and teaching more fun for both learners and teachers. This study will also show how a professional methodological support system and community can help teachers to use these modern 21st century teaching aids.